Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11356-013-1678-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dye degradation with reactive oxidants generated by chloride-induced peroxymonosulfate activation

Abstract: Transition-metal is known to catalyze peroxymonosulfate (PMS) decomposition to produce sulfate radicals. Here we report reactions between PMS and chloride, without a need of transition metals, also can be used to degrade organic dye pollutant (Rhodamine B, (RhB)). Some important operating parameters, such as dosages of PMS and Cl(-), pH of solution, temperature, ionic strength, and several common cations, were systematically investigated. Almost complete decoloration of RhB was achieved within 5 min ([PMS] = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…As shown in Fig. 4(a) < Na + , which was similar to the previous studies (Lou et al, 2003). However, NH 4 + was the major species responsible for AO7 degradation with the molar ratio of varying from 2:1 to 10:1.…”
Section: Effect Of the Molar Ratio Of [Nh 4 + ]/[Cl -]supporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Fig. 4(a) < Na + , which was similar to the previous studies (Lou et al, 2003). However, NH 4 + was the major species responsible for AO7 degradation with the molar ratio of varying from 2:1 to 10:1.…”
Section: Effect Of the Molar Ratio Of [Nh 4 + ]/[Cl -]supporting
confidence: 89%
“…It is known that NH 4 + hydrolyzes into neutral amine which may react with SO 4 •forming NH 2 • (Eqs. 4 and 5), a relatively weak oxidant (E 0 (NH 2 • /NH 3 ) = 0.6 V) (Lou et al, 2003;Nakamura et al, 2014;Neta et al, 1988).…”
Section: Effect Of Nh + Concentrationmentioning
confidence: 99%
“…The nitrating agent-Å NO 2 is likely to be directly oxidized by PMS (E 0 (HSO 5 À /HSO 4 À ) = 1.85 V vs NHE) possessing a higher standard redox potential than H 2 O 2 (E 0 (H 2 O 2 /H 2 O) = 1.77 V vs NHE) (Cotton et al, 1999). For example, our previous studies Lou et al, 2013) demonstrated that PMS can directly oxidize Cl À through two-electron transfer, producing reactive halogens (e.g. Cl 2 /HClO) (Eqs.…”
Section: ð17þmentioning
confidence: 99%
“…Previous investigations have focused on the impact of Cl − ions on the performance of different AOPs [6,[10][11][12][13]. However, in most cases the applicability of the selected AOPs was evaluated by assessing the degradation efficiency in saline wastewater.…”
Section: Introductionmentioning
confidence: 99%